Drivers of social network adoption in post-travel phase: An empirical study in Thai tourists - Nathatenee Gebsombut; Chien-ta Bruce Ho (Cogent Business & Management, 2019)
As tourism is a fast-growing industry, it is worth focusing on understanding travelers' information generation behavior. The previous research also found that research in the motivation of travelers in sharing travel information through SNSs is quite limited. This research aims to study social network site usage intention in the post-travel phase by adding information features, media features, and user factors. This paper used a quantitative approach with the SEM technique. Questionnaires completed by 450 Thai travelers were analyzed by using a structural equation modeling test. The results suggested that perceived usefulness, customer involvement, and information accuracy were the significant factors that enhanced travelers' social network site's adoption intention after their trip. Positive relationships existed between perceived usefulness, subjective norm, and accessibility factors positively influenced perceived usefulness. This study suggests that tourism businesses should create their SNSs accounts in well-known and easy accessed social media to increase the number of reviews and feedbacks. The present paper contributes to previous research by identifying the impact of the information feature, media features, social and user factors on social network sites adoption intention, specifically in the post-travel phase.
Keywords: 650; social network sites; behavioral intention; smart tourism technologies; technology acceptance